Design Optimization of Inductive Power Transfer Systems Considering Bifurcation and Equivalent AC Resistance for Spiral Coils - Alireza Namadmalan (16864236) (2020)
This paper presents a design optimization algorithm for series-series compensated Inductive Power Transfer (IPT) system based on flat spiral coils, considering bifurcation phenomenon and AC equivalent resistance of the coils. Moreover, it finds the best values in the areas where the IPT system operates in Zero Voltage Switching (ZVS) condition. Equivalent AC resistance of spiral coils is modeled based on eddy currents simulations using Finite Element Method (FEM) and Maxwell simulator. Based on the FEM simulations, a new approximation method using separation of variables is proposed as a function of spiral coil's main parameters. This paper shows that this model accurately derive equivalent resistance of the coils for a specific strand diameter, with almost 95% accuracy. Based on the proposed algorithm, several IPT systems are optimized in MATLAB software using Genetic Algorithm (GA). Finally, the proposed method has been verified using a laboratory prototype with output power of about 200 watts and operating frequency of about 85 kHz. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2020.3013120